The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s00276-016-1757-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the stylohyoid complex

Abstract: In conclusion, elongated and more medially deviated stylohyoid complexes are more frequent in males than in females. Their more frequent presence in the older age groups indirectly connects this phenomenon with the aging process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
2
5
1
1
Order By: Relevance
“…Although the classification criteria were different, in compliance with our study they reported that elongated SHC type was observed mostly in males. Unlikely the segmented type seen more often in females in our study (31.6% in females, 19.7% in males), Petrovic et al [32] reported that this type was observed more frequently in males.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Although the classification criteria were different, in compliance with our study they reported that elongated SHC type was observed mostly in males. Unlikely the segmented type seen more often in females in our study (31.6% in females, 19.7% in males), Petrovic et al [32] reported that this type was observed more frequently in males.…”
Section: Discussioncontrasting
confidence: 88%
“…Petrovic et al [32] evaluated gender and SHC morphology. They classified the SHC at six groups which were: normal appearance with up to 40 mm, normal appearance longer than 40 mm, bent, segmented, pseudoarticulated and styloid process with stylohyoid ligament distally ossified to the hyoid bone.…”
Section: Discussionmentioning
confidence: 99%
“…The styloid process and stylohyoid ligament ossification has been classified according to their shape and length as normal, elongated, bent, segmented, pseudoarticulated, and distally ossified and fixed to the lesser horn of the hyoid bone. The last type is the least frequently observed (Petrovi c et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Occipital artery and hypoglossal nerve lie laterally to the process. [1,2] SP length presents a large variability, ranging from 5 to 75mm [3]. A scientific global consensus defines that a SP longer than 30mm is considered elongated (Figures 1 and 2) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in the international literature exist, concerning the incidence of SP elongation, focused on different populations, including Indian, Turkish, Brazilian, Serbian and Italian [3,[8][9][10][11] Authorities. Specimen collection was random to eliminate any bias.…”
Section: Introductionmentioning
confidence: 99%